PAKISTANI EFL TEACHERS’ PERCEPTIONS ABOUT THE IMPACT OF EFL TEACHER EDUCATION UPON THEIR CLASSROOM TEACHING PRACTICES - Ikram Ullah; Dr. Muhammad Asif; Sanaullah Rustamani (International Journal of Contemporary Issues in Social Sciences, 2024)
This study employed qualitative data collection and analysis methods to investigate the effects of English as a foreign language teacher education programme on Pakistani teachers’ classroom teaching practices. Historically, Language teachers ‘education has been overlooked in Pakistan. Here, in this study, twenty in-service university teachers participated in semi-structured interviews. Thematic analysis was applied to the data collected from these interviews. Findings from the analysis established the effectiveness of Pre-Service and in- Service EFL Education. Results highlighted the weaknesses of EFL Education Program and also suggested for the improvement of EFL Education Programs. This study ends with a discussion of the implications of these findings.